Գեղամա երկիրն աշխարհագրական անվանումներում - Արմեն Ղարագյոզյան (ՀՀ ԳԱԱ հրատ.)
Географические названия — достоверные и неоценимые первоисточники и имеют большую познавательную ценность. Историко-сравнительный анализ древнеармянских топонимов может существенно расширить круг наших знаний об исторической Армении, содействуя восстановлению особенностей ее общественного, экономического, политического и культурного развития. В статье дается научное объяснение происхождению ряда топонимов страны Гегама (бассейн оз. Севан), что крайне необходимо для создания целостной истории данного региона. Place names are reliable and priceless sources, and they have great cognitive value. Historical comparative analysis of ancient Armenian place names may noticeably widen our knowledge about ancient Armenia, thus contributing to restore peculiarities of its social, economic, political and cultural evolution. This article gives new scientific explanation of the origin of some place names of the Geghama country (basin of the Lake Sevan), which is extremely necessary to recreate the entire history of this region.
Keywords: History; Topology; D History; G Geography; Anthropology; Recreation